Accounting Treatment of Travel Agent Package Revenue at Hotel X - Made Rania PURNAMANTHA; IGN Agung WIRYANATA; Ni Luh Riska YUSMARISA (Journal of Governance, Taxation and Auditing, 2026)
The purpose of this study is to determine the accounting treatment for revenue arising from travel agent packages. This study analyzes the process of recognizing, measuring, presenting, and disclosing travel agent package revenue in accordance with PSAK No. 72 of 2020. The research methodology used is a qualitative descriptive approach with a case study at the Conrad Bali Hotel. Data collection techniques were carried out through interviews, observations, and documentation of the Accounts Receivable, Chief Accountant, Income Audit, and Reservation departments. The results show that the Conrad Bali Hotel has implemented revenue accounting treatment systematically and according to standards. Revenue recognition is carried out using the accrual method, revenue measurement is based on the original price of services provided, revenue presentation in the income statement is not specifically separated from other hotel revenue, and disclosures include information regarding the amount of revenue obtained from the sale of the package.